Nuevo trato a las materias primas - Moran, Theodore H. (Estudios Internacionales, 1972)
Today’s strong trends toward economic nationalism have been providing many commodity-producing countries both the opportunity and the courage to drive out foreign investors. The first question one must ask in these cases is whether these nationalist countries, after finally achieving a certain degree of economic "independence" in the field of their raw materials, will be able to keep production on an efficient footing. In a vertically integrated, oligopolistic branch of industry, the possibilities open to nationalist groups depend on where the barriers to competition are located. Where barriers to competition remain under the control of nationalist governments, the interests of the country are better served if it maintains its place within the international oligopolistic system and ably abides by the accepted rules for that industrial branch.